Effect of bubble size on void fraction fluctuations in dispersed bubble flows. (October 2015) - Evgenidis, Sotiris P.; Karapantsios, Thodoris D.
Abstract : Graphical abstract: Highlights: Bubbly flow experiments resembling Decompression Sickness conditions in human bloodstream. A patented electrical technique is employed to register void fraction fluctuations down to 10 −5. The intensity and frequency of void fraction fluctuations depend strongly on bubble size. An empirical expression relates bubble size to void fraction statistical features. Abstract: It is known that bubble size affects seriously the average void fraction in bubbly flows where buoyant velocities vary considerably with bubble size. On the contrary, there is no systematic literature report about bubble size effects on the intensity and frequency of void fraction fluctuations around the average void fraction. This work aims to provide such information. An electrical impedance technique is employed along with non-intrusive ring electrodes to register void fraction fluctuations down to 10 −5 . Bubble size fluctuations are estimated from high resolution optical images. Experiments are conducted in co-current upward dispersed bubble flow inside a 21 mm tube with average bubble size between ∼50 and ∼700 μm. Water and blood simulant are used as test liquids with velocity from ∼3 to ∼30 cm s −1 . The above resemble conditions of Decompression Sickness (DCS) in the bloodstream of human vena cava. It is found that the intensity and frequency of void fraction fluctuations vary appreciably with bubble size at constant gas and liquid flow rates. Moreover, these variations are not random but scale with bubble size. As a first step to quantify this effect, an empirical expression is derived that relates average bubble size to the ratio standard deviation/average value of void fraction.